USE OF INNOVATIVE METHODS AND TOOLS IN ORGANIZING INDEPENDENT EDUCATION IN HIGHER EDUCATION COUNTRIES - AS A PEDAGOGICAL PROBLEM - Rashidova O., (FAN VA TA'LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
At present, the main part of the educational process in higher educational institutions is allocated to independent education, and this is considered as the main indicator of evaluating students' knowledge. Therefore, this article is devoted to the topic of innovative methods and means of organizing the independent education process in higher education institutions. In this article, first of all, what is independent education, and then the forms and means of organizing independent education are described. Students' independent works are discussed separately according to their characteristics. The importance of independent education in the educational process is scientifically and practically based. Formed on the basis of ehisting materials on ways to organize independent education. It is known that today many innovations have been made in independent education and modern, innovative methods and tools are being introduced to make it more useful for students. But despite this, the urgent issue of the present time in the higher education system is the proper organization of independent education and systematic work in its implementation, teaching students to work independently, creatively and socially active, socially - is to form a new generation of personnel who have the skills to find their place independently in political life. Therefore, in this article, the pedagogical problems of modern forms used in the organization of independent work of students, the low workload of independent education for students, the convenience of the task (that is, preparing a simple outline or summary in a manual notebook and preparing it by purchasing a ready-made one from computer services) problems are mentioned. Then, they will be tried to find ways to solve them using innovative methods and tools.